PTU-207 Outcome of anal cancer multidisciplinary team audit in a tertiary treatment centre. (22nd June 2015) - Body, S; Di Fabio, F; Chave, H; Nichols, P; Branagan, G; Nugent, K
Abstract : Introduction: Indications for anal cancer surgery for squamous cell carcinoma (SCC) are limited to selected early tumours and local treatment failure after radical chemoradiotherapy. The aim is to be able to offer Salvage surgery in at least 60% in patients with local relapse. This study reviewed our centre's results and compared them with the national audit standards for outcomes of anal cancer in patients undergoing chemoradiotherapy after discussion the multidisciplinary team (MDT). Method: Patients with anal SCC discussed at the Wessex anal cancer MDT meetings between 2010 and 2013 were retrospectively reviewed. Outcome measures were: proportion of salvage surgery offered, local control achieved, five-year post-salvage survival, delayed healing with plastic reconstruction and major (non-wound) morbidity – Clavien-Dindo ≥ 3. These were compared with the standards outlined by the Association of Coloproctology of Great Britain and Ireland. Results: A total of 126 patients were discussed at the MDT. Ninety-six patients had anal SCC. Of these, 66 patients underwent radical chemoradiotherapy with Mitomycin C and 5-Fluorouracil or Capecitabine. Fourteen (22%) patients developed local recurrence. Of these, 9 (64%) had salvage surgery and plastic reconstruction with a Vertical Rectus Abdominis Myocutaneous (VRAM) flap. The five-year overall survival of patients who had radical chemoradiotherapy was 92% with a median follow-up of 27 months and 89% for patients who had salvage surgery with a median follow up of 32 months (p = 0.60, log rank test). In patients having surgery, delayed healing with plastic reconstruction was 11% and major (non-wound) morbidity -Clavien-Dindo ≥ 3 was 22%. Conclusion: Long-term survival after radical chemoradiotherapy was achieved in the vast majority of patients even after salvage surgery and audit standards were fully met. Disclosure of interest: None Declared.